Chromosomal characterization in native populations of Elymus scabrifolius from Argentina through classical and molecular cytogenetics (FISH–GISH) - Tomas, Pablo Andrés (2012)
Karyotype of Elymus scabrifolius (2n=4x=28) was investigated by DAPI staining and Fluorescent In Situ Hybridization (FISH). All the accessions studied presented a symmetric and uniform karyotype constituted by 9 m + 3 m-sm + 2 sm. DAPI stain showed 1 to 7 conspicuous bands in all the chromosomes and polymorphisms between accessions were detected. FISH experiments carried out with the 45S rDNA probe (pTa71) showed strong hybridization signals on the metacentric SAT-chromosome pair No. 8; the submetacentric SAT-chromosome pair No. 13 presented weaker hybridization. FISH using pSc119.2 clone as probe let to identify five chromosome pairs. Then, the combination of chromosome morphology, DAPI-staining and FISH enabled the accurate identification of each chromosome pair in E. scabrifolius. GISH (Genomic In Situ Hybridization) experiments using Hordeum DNA as probe on mitotic metaphases confirmed unequivocally the presence of the H genome in E. scabrifolius, and enabled to observe six uniformly labeled chromosome pairs and two chromosome pairs with only one arm labeled. The remaining six chromosome pairs were weakly labeled. The rehybridization of FISH slides with Hordeum DNA probe let to assign the genomic provenance of most of chromosomes in the studied accessions. Moreover, intergenomic rearrangement was detected between genome H and the still unknown progenitor genome.